The use of multi-state life tables in estimating places for biomedical and behavioral scientists : a technical paper (Compass series (Washington, D.C.), 1997)
This report begins by providing an overview of demographic modeling, including the strengths and weaknesses of this technique. Then the elements of the model are developed (e.g., workforce inflows and outflows are defined) and the data set used for estimation of the model--the Survey of Doctorate Recipients (SDR)--is described. Next, the calculation of transition rates for various life changes (e.g., retirement, changing profession) is described. At this point, the model is used to make retroactive projections that are tested against real data from the SDR. Finally, the panel presents recommendations for further work that is needed to develop the model so that it can be used to project the needs for biomedical and behavioral scientists.